Economic of Chambal Ravine Afforestation - Peri, D. N.; Khybri, M. L. (Indian Forester, 1975)
Out of 3.6 million hectare of land affected by ravines 0.4 million hectare lie in Rajasthan. Studies undertaken by Soil Conservation Research, Demonstration and Training Centre, Kota for reclamation and eventually utilising Chambal ravines, indicate that the area should be fenced; provide peripheral bund, vegetative check dams in the gully-beds and raise plantation of Acacia nilotica and Prosopis juliflora and grasses such as Dichanthium annulatum and Cenchrus ciliaris in the top and side slopes. In the gully bed Dendrocalamus strichus (bamboos) is raised successfully. According to the ’Faustmans’ formula net income that can be obtained from such lands works out to Rs. 349/- per ha per annum.